HOXB5 acts as an oncogenic driver in head and neck squamous cell carcinoma via EGFR/Akt/Wnt/β-catenin signaling axis. Issue 6 (June 2020) - Lee, Kyungmin; Chang, Jae Won; Oh, Chan; Liu, Lihua; Jung, Seung-Nam; Won, Ho-Ryun; Kim, Young Il; Rha, Ki-Sang; Koo, Bon Seok
Abstract: Introduction: Identification of therapeutic targets in head and neck squamous cell carcinoma (HNSCC) is essential because most of the patients with advanced HNSCC have a poor prognosis. Homeobox genes constitute a large cluster of transcription factors with important regulatory roles in mammalian embryonic development and cell differentiation. The oncogenic role of homeobox B5 (HOXB5) in HNSCC has not been investigated. Materials and methods: We used The Cancer Genome Atlas (TCGA) data to evaluate the correlations between HOXB5 expression and various HNSCC clinicopathological factors. We knocked down HOXB5 expression in HNSCC cell lines and explored the in vitro and in vivo effects on cell proliferation and motility, and HOXB5 signaling. Results: The Cancer Genome Atlas (TCGA) data shows that HOXB5 is overexpressed in HNSCC compared to normal tissues and significantly associates with tumor stage ( P  = 0.003), lymph node metastasis ( P  = 0.031), disease stage ( P  = 0.002), and angiolymphatic invasion ( P  = 0.004). Our results also show that HOXB5 expression is up-regulated in HNSCC cell lines, and HOXB5 knockdown significantly reduced cell proliferation and tumor growth in vitro and in vivo. Inhibition of HOXB5 decreases cell migration and invasion via suppression of epithelial-to-mesenchymal transition (EMT)-associated proteins expression. Moreover, HOXB5 directly binds to the promoter region of EGFR and consequently regulates the activity of the Akt/Wnt/β-catenin signaling axis. Conclusion: HOXB5 may be a novel therapeutic target as an oncogenic driver by regulating EGFR transcription in HNSCC.